Economies alternatives en contexte frontalier. La contrebande entre le Luxembourg et la France pendant l’entre-deux-guerres - Portas Vázquez, Irene (Hémecht. Zeitschrift für Luxemburger Geschichte = Revue d’histoire luxembourgeoise, 2025)
Abstract: „Borders are often studied as sites of struggle, power relations and political friction, but they have also been places of human life, exchange and circulation. This article examines smuggling between Luxembourg and France during the interwar period, exploring often-overlooked aspects of this border region’s socio-economic fabric, such as the role of women and children, hardships in times of economic downturn, foodstuffs, consumption patterns and family relations across these two countries. Smuggling demonstrates how the Franco-Luxembourg border creates alternative economies and becomes a resource for individuals living in this mining and industrial basin.“
Keywords: Schmuggel